Corrective Feedback in the Digital Learning: The Use of Google Classroom - Farhrul Rozi; Farhan Arifin; Ani Susianti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Corrective feedback comes as a crucial aspect for majority of students in digital learning especially during this Covid-19 outbreak. As a reason, the students need to receive more information from their own teachers so as to achieve the learning outcomes regarding the material understanding. Based on the statement mentioned, it might be benefits and challenges perceived by the students towards the corrective feedback in the online learning process since the digital learning does not lead them to have learning satisfaction compared to the offline learning with comprehensive learning interaction of classroom activity.  This research was aimed at investigating the benefits and challenges of corrective feedback perceived by the students in the digital learning through the use of Google Classroom. The phenomenology of qualitative study was employed in this study by using interview as the research instrument. Besides, this research was conducted at an Islamic private university in Yogyakarta concerning on Master of English Language Education. The study employed six Master’s degree students of English Language Education who had enrolled in some courses during the digital learning process. Thereupon, the data analysis of this research was conducted by transcribing the interview, applying coding called as open coding, analytical coding, axial coding and selective coding as well as explaining and elaborating research findings in the results and discussion supported by the appropriate theories from the experts. In addition, the researchers had found several findings related to benefits and challenges of corrective feedback perceived by the students in the digital learning. As the benefits of corrective feedback, those were developing writing skill, becoming a guideline for doing the assignments, understanding strengths and weaknesses of writing skill, becoming a habit to write an academic essay, and building grammar understanding in writing skill. Of the challenges in the corrective feedback, those were facing the difficulty to understand the general comments, receiving long duration feedback, providing unequal feedback distribution, giving a limited access for having communication with the lecturers, receiving unclear information towards the feedback content of the writing assignments, providing lack of essay writing examples, and receiving a limited feedback information.